Preparation method of multilayer reinforced alkaline water composite diaphragm
By using PEEK braided mesh as the reinforced framework layer in the composite diaphragm, the problem of insufficient mechanical strength and heat resistance in the existing diaphragm in high-temperature alkaline electrolytic cells is solved, and higher diaphragm performance and safety are achieved.
Patent Information
- Application Number
- CN202411259366.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-14
AI Technical Summary
When used in high-temperature alkaline electrolytic cells, the mechanical strength and heat resistance characteristics are insufficient, and they are prone to cracking and corrosion, resulting in safety hazards and performance attenuation of the electrolytic cells.
The preparation method of multi-layer reinforced alkali and water composite separator is adopted, and a composite film with high hydrophilicity, heat resistance and mechanical strength is formed through specific slurry formulations and film making processes.
It significantly improves the heat resistance and safety of the diaphragm, enhances its tensile strength, ion permeability and surface resistance, reduces the cost of the diaphragm, and improves electrochemical performance and safety reliability.
Smart Images

Figure CN119433615A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite diaphragm preparation methods, and in particular to a preparation method of a multi-layer enhanced alkaline-water composite diaphragm. Background Art
[0002] At present, fossil fuel hydrogen production, which is mature in technology and low in cost, is still the main hydrogen supplier in the early stage of my country's hydrogen energy industry development. Industrial byproduct hydrogen serves as a low-cost transitional hydrogen source in the medium term, playing a supplementary role in the distributed hydrogen source market. In the long run, the proportion of hydrogen production from water electrolysis, which is cleaner and more efficient, will gradually expand, and gradually replace fossil fuel hydrogen production to become the main hydrogen supplier in the market.
[0003] According to the working principle and electrolyte, water electrolysis hydrogen production technology can be divided into four types: alkaline water electrolysis (ALK), proton exchange membrane water electrolysis (PEM), high temperature solid oxide water electrolysis (SOEC) and anion exchange membrane water electrolysis (AEM). The mainstream technology route is alkaline water electrolysis equipment (ALK) technology, which has completed the commercialization process and occupies a dominant position in the market. PEM technology is still in the early stage of commercialization due to cost constraints, and SOEC and AEM technologies are still in the research and development stage.
[0004] Diaphragm material is an important component of alkaline electrolyzer, and its main functions include three aspects: ① Separating cathode and anode to form cathode and anode chambers to prevent short circuit; ② Avoid mixing of gas products at both poles; ③ Having high ion conductivity to facilitate the transfer of hydroxide ions from cathode to anode. Therefore, the ideal diaphragm material should have the following characteristics: ① Good ion conductivity, high porosity, and low resistivity; ② High gas barrier, high hydrophilicity, and high corrosion resistance; ③ Thin thickness, small pore size, high mechanical strength, and good dimensional stability; ④ Low cost and long service life. The quality of the diaphragm is directly related to the purity and power consumption of H2 and O2.
[0005] The hottest diaphragm in domestic and foreign research is the third generation of organic-inorganic composite diaphragm, which is composed of slurry coated on both sides of the pps substrate. Taking Agfa's ZIRFON product as an example, the surface coating slurry contains zirconium dioxide and polymer, among which inorganic oxide nanoparticles such as zirconium dioxide are the main substances to improve its hydrophilicity. The mechanism of improving hydrophilicity may be that the oxygen ions in zirconium oxide form hydrogen bonds with water in the electrolyte. Therefore, the main purpose of surface coating is to improve the hydrophilicity of the diaphragm, improve the compatibility of the diaphragm with the electrolyte, and reduce the internal resistance of the electrolytic cell. However, the composite diaphragm with pps as the supporting mesh has relatively weak mechanical strength and heat resistance, and is easy to crack and puncture during the assembly process of the electrolytic cell. Long-term high-concentration potassium hydroxide immersion corrosion causes the physical and chemical properties of the diaphragm to decay rapidly, resulting in coating shedding, gas leakage between the anode and cathode, and explosion hazards in the electrolytic cell. Summary of the invention
[0006] In order to overcome the above problems existing in the prior art, the present invention provides a method for preparing a multi-layer enhanced alkali-water composite diaphragm.
[0007] The present invention discloses a method for preparing a multi-layer enhanced alkaline-water composite diaphragm, comprising the following steps:
[0008] Step S1: preparing raw materials; the raw materials include polysulfone, zirconium dioxide, polyethylene glycol, polyvinyl pyrrolidone, potassium chloride, methyl pyrrolidone and PEEK woven mesh;
[0009] Step S2: slurry preparation;
[0010] Step S3: film formation.
[0011] On this basis, the ratio of polysulfone to zirconium dioxide is 1:3-5.
[0012] On this basis, the ratio of polysulfone to polyethylene glycol is 1:0.2-1.
[0013] On this basis, the ratio of polysulfone to polyvinyl pyrrolidone is 1:0.2-0.5.
[0014] On this basis, the ratio of polysulfone to potassium chloride is 1:0.01-0.08.
[0015] On this basis, the ratio of the polysulfone to methyl pyrrolidone is 1:4-8.
[0016] On this basis, the thickness of the PEEK is 30 to 80 μm.
[0017] On this basis, the slurry preparation method of step 2 comprises the following steps:
[0018] Step S21: heating and dispersing polysulfone in methyl pyrrolidone at 60-100° C. to obtain a uniform and transparent polymer solution;
[0019] Step S22: adding zirconium oxide, dispersing at a high speed of 500 to 1500 r / min for 2 to 8 hours, then adding polyethylene glycol, polyvinyl pyrrolidone and potassium chloride in sequence, and continuing stirring at 200 to 600 r / r / min for 2 to 8 hours;
[0020] Step S23: After the solution forms a homogeneous system, vacuum degassing is performed for 3 to 8 hours to obtain a milky white slurry.
[0021] On this basis, the film making method of step S3 comprises the following steps:
[0022] Step S31: the release PET backing film is pulled out from the unwinding mechanism, passes through the guide roller to change the film feeding direction, and then enters the slurry coating unit;
[0023] Step S32: The release film is at the back roller of the slurry coating unit, and the slurry is transported from the transfer tank to the extrusion die head through a pipeline via a screw pump, and is scraped on the back film to form a layer of slurry.
[0024] Step S33: the film strip moves to the pressing roller mechanism, and the PEEK mesh is pre-laminated with the wet slurry of the primer through the pressing roller mechanism;
[0025] Step S34: the membrane tape moves to the extrusion die, is transported to the extrusion die by a screw pump, and a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh.
[0026] Step S35: the membrane belt continues to move forward and directly enters the coagulation bath unit, where the wet slurry membrane undergoes a phase transition, and after 5 to 20 minutes, a solidified organic-inorganic composite membrane is finally formed.
[0027] On this basis, in step S35, the coagulation bath unit is kept at a constant temperature.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) PEEK woven mesh is used as the reinforcing skeleton layer. The melting point of PEEK material is 340℃, while the melting point of PPS is about 280℃. The heat resistance of PEEK material is significantly higher than that of PPS mesh. In the future, the heat resistance and safety of the diaphragm will be greatly improved for the application of high-temperature alkaline electrolytic cells (>100℃).
[0030] (2) Compared with PPS material, PEEK material has higher hydrophilicity and the carbon group on the main chain has greater polarity, which can easily form a physical bond with ceramic powder, thereby improving the adhesion between ceramic powder and substrate;
[0031] (3) The thickness of the PEEK mesh used in the electrolytic cell is 50μm to 200μm, and the porosity is 40% to 75%. The innovative PEEK mesh multilayer reinforced composite technology is proposed to prepare the composite diaphragm. Compared with the single-layer pps alkaline composite diaphragm, its tensile strength, ion permeability, surface resistance, and puncture strength are significantly improved. The thickness can be made thinner, reducing the cost of the diaphragm, while improving the electrochemical performance and safety reliability;
[0032] (4) This technology realizes the mass production of at least 2 layers of reinforced skeleton composite membranes, and the product performance is better than similar products currently on the market. The molecular weight of the resin used for the weaving of PEEK mesh is: Mw is 80,000 to 120,000, and the thickness of the multi-layer reinforced composite membrane is 150-500μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a structural schematic diagram of the coating process of the multi-layer reinforcement mesh of the present invention;
[0034] Figure 2 It is a schematic diagram of the structure of the PEEK reinforced mesh layer of the present invention;
[0035] Figure 3 Schematic diagram of SEM structure of composite diaphragm surface;
[0036] Figure 4 Schematic diagram of the SEM structure of the composite diaphragm cross section;
[0037] In the figure: 1. unwinding mechanism, 2. guide roller, 3. slurry coating unit, 4. coagulation bath unit, 11. first extrusion die, 12. first pressing roller mechanism, 13. second extrusion die, 14. second pressing roller mechanism, 15. third extrusion die, 16. third pressing roller mechanism, 17. fourth extrusion die, 18. fourth pressing roller mechanism, 19. fifth extrusion die, 20. fifth pressing roller mechanism, 21. sixth extrusion die. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] The present invention discloses a method for preparing a multilayer enhanced alkaline-water composite diaphragm, comprising the following steps:
[0040] Step S1: raw material preparation; the raw materials include polysulfone, zirconium dioxide, polyethylene glycol, polyvinyl pyrrolidone, potassium chloride, methyl pyrrolidone and PEEK woven mesh, the ratio of polysulfone to zirconium dioxide is 1:3-5; the ratio of polysulfone to polyethylene glycol is 1:0.2-1; the ratio of polysulfone to polyvinyl pyrrolidone is 1:0.2-0.5; the ratio of polysulfone to potassium chloride is 1:0.01-0.08; the ratio of polysulfone to methyl pyrrolidone is 1:4-8; reference Figure 2 , the thickness of PEEK is 30-80 μm;
[0041] Step S2: slurry preparation; specifically: Step S21: at 60-100°C, heat and disperse the polysulfone in methyl pyrrolidone to obtain a uniform and transparent polymer solution; Step S22: add zirconium oxide, disperse at a high speed of 500-1500r / min for 2-8h, then add polyethylene glycol, polyvinyl pyrrolidone and potassium chloride in sequence, and continue stirring at 200-600r / min for 2-8h; Step S23: after the solution forms a homogeneous system, vacuum degassing for 3-8h to obtain a milky slurry.
[0042] Step S3: Film making, specifically: Step S31: The release PET back film is pulled out from the unwinding mechanism 1, and after changing the film feeding direction through the guide roller 2, it enters the slurry coating unit 3; Step S32: At the first back roller of the slurry coating unit, the slurry in the transfer tank is transported to the extrusion die head through a pipeline by a screw pump, and a layer of slurry is scraped on the back film; Step S33: The film belt moves to the pressure roller mechanism, and the PEEK mesh is pre-laminated with the wet slurry of the primer through the pressure roller mechanism; Step S34: The film belt moves to the extrusion die head, and a layer of slurry with a wet thickness of 80μm is scraped on the PEEK mesh; Step S35: The film belt continues to move forward and directly enters the coagulation bath unit 4. The coagulation bath unit 4 maintains a constant temperature and the wet slurry film undergoes a phase transition inside. After 5 to 20 minutes, a cured organic-inorganic composite film is finally formed.
[0043] The prepared composite diaphragm structure reference Figure 4 .
[0044] Example 1
[0045] Raw material preparation: 1 part of polysulfone, 3 parts of (D50, 0.5 μm) zirconium dioxide, 0.5 parts of polyethylene glycol, 0.2 parts of polyvinyl pyrrolidone, 0.05 parts of potassium chloride, 6 parts of methyl pyrrolidone and 50 μm thick PEEK woven mesh;
[0046] Preparation of slurry: Heat 1 part of polysulfone at 80°C and disperse it in 6 parts of methyl pyrrolidone to obtain a uniform and transparent polymer solution, add 3 parts of zirconium oxide, disperse it at 800r / min for 3 hours, then add 0.5 parts of polyethylene glycol, 0.2 parts of polyvinyl pyrrolidone, and 0.01 parts of potassium chloride in sequence, continue stirring at 400r / min for 3 hours, and after the solution forms a homogeneous system, vacuum degas for 6 hours to obtain a milky white slurry;
[0047] Film making method: refer to Figure 1As shown, the release PET back film is pulled out from the unwinding mechanism 1, and after the film feeding direction is changed by the guide roller 2, it enters the slurry coating unit 3. At the first back roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die 11 by a pipeline through a screw pump, and a layer of wet slurry with a thickness of 80 μm is scraped on the back film. The film belt moves to the first pressing roller mechanism 12, and the PEEK mesh is pressed down by the first pressing roller mechanism 12 to pre-laminate with the wet slurry of the primer. The film belt moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump. On the PEEK mesh, a layer of wet slurry with a thickness of 80 μm is scraped. A layer of slurry with a wet thickness of 80 μm is applied, and the film belt moves to the second pressing roller mechanism 14. The PEEK mesh is pressed down by the second pressing roller mechanism 14 and pre-laminated with the wet slurry with the PEEK mesh. The film belt moves to the third extrusion die 15 and is transported to the third extrusion die 15 by a screw pump. A layer of slurry with a wet thickness of 70 μm is scraped on the PEEK mesh. The film belt continues to move forward and directly enters the coagulation bath unit 4. The coagulation bath unit 4 maintains a constant temperature, and the wet slurry film undergoes a phase transition inside. After 8 minutes and 5 to 20 minutes, a cured organic-inorganic composite membrane HQT1 is finally formed.
[0048] Example 2
[0049] The difference between Example 2 and Example 1 is that: the release PET back film is pulled out from the unwinding mechanism 1, passes through the guide roller 2 to change the film feeding direction, and then enters the slurry coating unit 3. At the first back roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die head 11 through a pipeline through a screw pump, and a layer of slurry with a wet thickness of 90 μm is scraped on the back film. The film belt moves to the first pressing roller mechanism 12, and the PEEK mesh passes through the first pressing roller mechanism 12. The roller mechanism 12 presses down and pre-laminates the wet slurry of the primer, and the film strip moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump. A layer of slurry with a wet thickness of 90 μm is scraped on the PEEK mesh. The film strip moves to the second pressing roller mechanism 14, and the PEEK mesh is pressed down by the second pressing roller mechanism 14 to pre-laminate the wet slurry with the PEEK mesh. The film strip moves to the third extrusion die 15, and is transported to the third extrusion die 16 by a screw pump. 5, a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh, the film belt moves to the third pressing roller mechanism 16, the PEEK mesh is pressed down by the third pressing roller mechanism 16 and pre-bonded with the wet slurry with the PEEK mesh, the film belt moves to the fourth extrusion die 17, and is transported to the fourth extrusion die 17 by a screw pump, and a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh, and the film belt continues to move forward and directly enters the coagulation bath unit 4, the unit maintains a constant temperature, and the wet slurry film undergoes a phase transition inside, and after 9 minutes, a solidified organic-inorganic composite membrane HQT2 is finally formed.
[0050] Example 3
[0051] The difference between Example 3 and Example 1 is that the release PET back film is pulled out from the unwinding mechanism 1, passes through the guide roller 2 to change the film feeding direction, and then enters the slurry coating unit 3. At the first back roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die 11 through a pipeline through a screw pump, and a layer of slurry with a wet thickness of 90 μm is scraped on the back film. The film belt moves to the first pressing roller mechanism 12, and the PEEK mesh passes through the first pressing roller mechanism 12. The roller mechanism 12 presses down and pre-laminates the wet slurry of the primer, and the film tape moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump. A layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh. The film tape moves to the second pressing roller mechanism 14, and the PEEK mesh is pressed down by the second pressing roller mechanism 14 to pre-laminate the wet slurry with the PEEK mesh. The film tape moves to the third extrusion die 15, and is transported to the third extrusion die 16 by a screw pump. 5, a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh, the film belt moves to the third pressing roller mechanism 16, the PEEK mesh is pressed down by the third pressing roller mechanism 16 and pre-laminated with the wet slurry with the PEEK mesh, the film belt moves to the fourth extrusion die head 17, and is transported by a screw pump to the fourth extrusion die head 17, a layer of slurry with a wet thickness of 85 μm is scraped on the PEEK mesh, the film belt moves to the fourth pressing roller mechanism 18, the PEEK mesh After being pressed down by the fourth pressing roller mechanism 18 and pre-laminated with the wet slurry with PEEK mesh, the film tape moves to the fifth extrusion die 19, and is transported to the fifth extrusion die 19 by a screw pump. A layer of slurry with a wet thickness of 85 μm is scraped on the PEEK mesh. The film tape then continues to move forward and directly enters the coagulation bath unit 4. The unit maintains a constant temperature, and the wet slurry film undergoes a phase transition inside. After 11 minutes, a solidified organic-inorganic composite film HQT3 is finally formed.
[0052] Example 4
[0053] The difference between Example 4 and Example 1 is that the release PET back film is pulled out from the unwinding mechanism 1, passes through the guide roller 2 to change the film feeding direction, and then enters the slurry coating unit 3. At the first back roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die head 11 through a pipeline through a screw pump, and a layer of slurry with a wet thickness of 100 μm is scraped on the back film. The film belt moves to the first pressing roller mechanism 12, and the PEEK mesh passes through the first The pressing roller mechanism 12 presses down and pre-laminates the wet slurry of the primer, and the film tape moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump. A layer of slurry with a wet thickness of 90 μm is scraped on the PEEK mesh. The film tape moves to the second pressing roller mechanism 14, and the PEEK mesh is pressed down by the second pressing roller mechanism 14 to pre-laminate the wet slurry with the PEEK mesh. The film tape moves to the third extrusion die 15, and is transported to the third extrusion die 16 by a screw pump. 5, a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh, the film belt moves to the third pressing roller mechanism 16, the PEEK mesh is pressed down by the third pressing roller mechanism 16 and pre-laminated with the wet slurry with the PEEK mesh, the film belt moves to the fourth extrusion die head 17, and is transported by the screw pump to the fourth extrusion die head 17, a layer of slurry with a wet thickness of 90 μm is scraped on the PEEK mesh, the film belt moves to the fourth pressing roller mechanism 18, the PEEK mesh is pressed down by the fourth pressing roller mechanism 18 and pre-laminated with the wet slurry with the PEEK mesh, and the film belt moves to the fifth extrusion die head 19, the fifth extrusion die 19 is transported by a screw pump, and a layer of slurry with a wet thickness of 70μm is scraped on the PEEK mesh. The film strip moves to the fifth pressing roller mechanism 20, and the PEEK mesh is pressed down by the fifth pressing roller mechanism 20 to pre-bond with the wet slurry with the PEEK mesh. The film strip moves to the sixth extrusion die 21, and the sixth extrusion die 21 is transported by a screw pump, and a layer of slurry with a wet thickness of 30μm is scraped on the PEEK mesh. The film strip continues to move forward and directly enters the coagulation bath unit 4. The unit maintains a constant temperature, and the wet slurry film undergoes a phase transition inside. After 1 1min, a cured organic-inorganic composite membrane HQT4 is finally formed.
[0054] Example 5
[0055] The difference between Example 5 and Example 1 is that the release PET backing film is pulled out from the unwinding mechanism 1, passes through the guide roller 2 to change the film feeding direction, and then enters the slurry coating unit 3. At the first backing roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die head 11 through a pipeline through a screw pump, and a layer of slurry with a wet thickness of 80 μm is scraped on the backing film. The film belt moves to the first pressing roller mechanism 12, and the PEEK mesh passes through the first pressing roller mechanism 12. The roller mechanism 12 is pressed down to pre-laminate with the wet slurry of the primer, and the film tape moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump, and a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh. The film tape moves to the second pressing roller mechanism 14, and the PEEK mesh is pressed down by the third pressing roller mechanism 14 to pre-laminate with the wet slurry with the PEEK mesh. The film tape moves to the third extrusion die 15, and is transported to the third extrusion die 15 by a screw pump, and a layer of slurry with a wet thickness of 70 μm is scraped on the PEEK mesh. The film tape then continues to move forward and directly enters the coagulation bath unit 4, which maintains a constant temperature, and the wet slurry film undergoes a phase transition inside. After 10 minutes, a cured organic-inorganic composite film HQT5 is finally formed.
[0056] Comparative Example 1
[0057] Raw material preparation: 1 part of polysulfone, 3 parts of (D50, 0.5 μm) zirconium dioxide, 0.5 parts of polyethylene glycol, polyvinyl pyrrolidone, 0.05 parts of potassium chloride, 6 parts of methyl pyrrolidone and 50 μm thick pps woven mesh;
[0058] Preparation of slurry: Heat and disperse 1 part of polysulfone in 6 parts of methyl pyrrolidone at 80°C to obtain a uniform and transparent polymer solution, add 3 parts of zirconium oxide, disperse at 800r / min for 3h, then add 0.5 parts of polyethylene glycol, 0.2 parts of polyvinyl pyrrolidone, and 0.01 parts of potassium chloride in sequence, continue stirring at 400r / min for 3h, and after the solution forms a homogeneous system, vacuum degas for 6h to obtain a milky white slurry;
[0059] Film making method: refer to Figure 1As shown, the release PET back film is pulled out from the unwinding mechanism 1, and after the film feeding direction is changed by the guide roller 2, it enters the slurry coating unit 3. At the first back roller of the slurry coating unit 3, the slurry in the transfer tank is transported to the first extrusion die 11 by a pipeline through a screw pump, and a layer of slurry with a wet thickness of 120 μm is scraped on the back film. The film belt moves to the first pressing roller mechanism 12, and the pps mesh is pressed down by the first pressing roller mechanism 12 to pre-bond with the wet slurry of the primer. The film belt moves to the second extrusion die 13, and is transported to the second extrusion die 13 by a screw pump. A layer of slurry with a wet thickness of 95 μm is scraped on the pps mesh. The film belt continues to move forward and directly enters the coagulation bath unit 4. The unit maintains a constant temperature, and the wet slurry film undergoes a phase transition inside. After 8 minutes and 5 to 20 minutes, a cured organic-inorganic composite film PQT1 is finally formed.
[0060] The performances are shown in Table 1 below:
[0061]
[0062]
[0063] Table 1
[0064] In summary, PEEK woven mesh is used as the reinforcing skeleton layer. The melting point of PEEK material is 340℃, while the melting point of pps is about 280℃. The heat resistance of PEEK material is significantly higher than that of pps mesh. In the future, the heat resistance and safety of the diaphragm will be greatly improved for the application of high-temperature alkaline electrolytic cells (>100℃).
[0065] Secondly, PEEK material is more hydrophilic than PPS material, and the carbon group on the main chain has a larger polarity, which can easily form a physical bond with the ceramic powder, thereby improving the adhesion between the ceramic powder and the substrate.
[0066] The thickness of the PEEK woven mesh used in the electrolytic cell is 50μm to 200μm, and the porosity is 40% to 75%. The innovative PEEK woven mesh multi-layer reinforced composite technology is proposed to prepare the composite diaphragm. Compared with the single-layer pps alkaline composite diaphragm, its tensile strength, ion permeability, surface resistance, and puncture strength are significantly improved. The thickness can be made thinner, reducing the cost of the diaphragm, while improving the electrochemical performance and safety reliability;
[0067] This technology realizes the batch production of at least 2 layers of reinforced skeleton composite membranes. The product performance is better than similar products currently on the market. The molecular weight of the resin used for PEEK mesh is: Mw is 80,000 to 120,000, and the thickness of the multi-layer reinforced composite membrane is 150-500μm.
[0068] The above description shows and describes the preferred embodiments of the present invention. As mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a multi-layer enhanced alkaline water composite membrane, characterized in that: The following steps are involved: Step S1: preparing raw materials; the raw materials include polysulfone, zirconium dioxide, polyethylene glycol, polyvinyl pyrrolidone, potassium chloride, methyl pyrrolidone and PEEK woven mesh; Step S2: slurry preparation; Step S3: film formation.
2. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 1, characterized in that: The ratio of the polysulfone to the zirconium dioxide is 1:3-5.
3. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 2, characterized in that: The ratio of the polysulfone to the polyethylene glycol is 1:0.2-1.
4. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 3, characterized in that: The ratio of the polysulfone to the polyvinyl pyrrolidone is 1:0.2-0.
5.
5. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 4, characterized in that: The ratio of polysulfone to potassium chloride is 1:0.01-0.
08.
6. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 5, characterized in that: The ratio of the polysulfone to the methyl pyrrolidone is 1:4-8.
7. The method for preparing the multi-layer reinforced alkaline water composite membrane according to claim 6, characterized in that: The thickness of the PEEK is 30-80 μm.
8. The method for preparing the multi-layer enhanced alkaline water composite membrane according to claim 1, characterized in that: The slurry preparation method of step 2 comprises the following steps: Step S21: heating and dispersing polysulfone in methyl pyrrolidone at 60-100° C. to obtain a uniform and transparent polymer solution; Step S22: adding zirconium oxide, dispersing at a high speed of 500 to 1500 r / min for 2 to 8 hours, then adding polyethylene glycol, polyvinyl pyrrolidone and potassium chloride in sequence, and continuing stirring at 200 to 600 r / min for 2 to 8 hours; Step S23: After the solution forms a homogeneous system, vacuum degassing is performed for 3 to 8 hours to obtain a milky white slurry.
9. The method for preparing the multi-layer enhanced alkaline water composite diaphragm according to claim 1, characterized in that: The film making method of step S3 comprises the following steps: Step S31: the release PET backing film is pulled out from the unwinding mechanism (1), passes through the guide roller (2) to change the film feeding direction, and then enters the slurry coating unit (3); Step S32: The release film is at the back roller of the slurry coating unit (3), and the slurry is transported from the transfer tank to the extrusion die head through a pipeline via a screw pump, and a layer of slurry is scraped on the back film to form a layer of slurry; Step S33: the film strip moves to the pressing roller mechanism, and the PEEK mesh is pre-laminated with the wet slurry of the primer through the pressing roller mechanism; Step S34: the membrane tape moves to the extrusion die, is transported to the extrusion die by a screw pump, and a layer of slurry with a wet thickness of 80 μm is scraped on the PEEK mesh; Step S35: The membrane strip continues to move forward and directly enters the coagulation bath unit (4), where the wet slurry membrane undergoes a phase transition, and after 5 to 20 minutes, a solidified organic-inorganic composite membrane is finally formed.
10. The method for preparing the multi-layer reinforced alkaline water composite diaphragm according to claim 9, characterized in that: In step S35, the coagulation bath unit (4) is kept at a constant temperature.
Citation Information
Patent Citations
High-conductivity alkali-resistant water electrolytic cell composite diaphragm and preparation method thereof
CN115449844A
Preparation method of novel microporous diaphragm for alkaline electrolyzed water, obtained product and application
CN116024825A
Conductive oxide doped composite diaphragm and preparation method thereof
CN117265588A
Composite slurry, porous diaphragm as well as preparation method and application of porous diaphragm
CN117305904A
Composite diaphragm, preparation method thereof and application in preparation of diaphragm for producing hydrogen by electrolyzing water
CN117328102A
Cited By
Preparation method for multilayer reinforced alkali-water composite separator
WO2026052108A1